The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1061/(asce)1084-0699(2007)12:4(394)
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Tail Dependence in Bivariate Frequency Analysis

Abstract: This paper highlights the importance of taking into account the tail dependence in the context of bivariate frequency analysis based on copulas. Three nonparametric estimators of the tail-dependence coefficient are compared by simulations with seven families of copulas. We choose the two estimators most adapted to a bivariate frequency analysis of the annual maximum flows and the corresponding flow hydrograph volumes of the Loire River ͑France͒. In this example, the bivariate return period and the conditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
123
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(129 citation statements)
references
References 44 publications
6
123
0
Order By: Relevance
“…These works provide quite extensive simulation studies devised to assess the reliability of a set of parametric and nonparametric k U estimators as well as several conclusive warnings about their use in practical analyses. Poulin et al (2007) made an ad hoc Monte Carlo experiment to choose the most appropriate estimator for a specific case study, retaining the Coles-Heffernan-Tawn k CHT U estimator (Coles et al 1999) and Capéraà-Fougères-Genest k CFG U estimator (Capéraà et al 1997). Poulin et al (2007) also stressed the caveats previously reported by Schmidt (2003) and Frahm et al (2005).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…These works provide quite extensive simulation studies devised to assess the reliability of a set of parametric and nonparametric k U estimators as well as several conclusive warnings about their use in practical analyses. Poulin et al (2007) made an ad hoc Monte Carlo experiment to choose the most appropriate estimator for a specific case study, retaining the Coles-Heffernan-Tawn k CHT U estimator (Coles et al 1999) and Capéraà-Fougères-Genest k CFG U estimator (Capéraà et al 1997). Poulin et al (2007) also stressed the caveats previously reported by Schmidt (2003) and Frahm et al (2005).…”
Section: Introductionmentioning
confidence: 96%
“…Poulin et al (2007) made an ad hoc Monte Carlo experiment to choose the most appropriate estimator for a specific case study, retaining the Coles-Heffernan-Tawn k CHT U estimator (Coles et al 1999) and Capéraà-Fougères-Genest k CFG U estimator (Capéraà et al 1997). Poulin et al (2007) also stressed the caveats previously reported by Schmidt (2003) and Frahm et al (2005). Serinaldi (2008) exploited the relationship between k U and Kendall correlation coefficient s K to build a diagnostic plot useful for the model selection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Malevergne and Sornette [2003] the authors showed that the usual Gaussian type of dependence is not appropriate to estimate financial risks, since it underestimates the dependence of extremes. There are several hydrological applications, most of them related to the analysis of extremes [Salvadori et al, 2007;Favre et al, 2004;Poulin et al, 2007].…”
Section: Introductionmentioning
confidence: 99%